Oral Health and Its Aetiological Role in Behcet's Disease - MUMCU, GONCA (FRONTIERS MEDIA SA, 2021)
Behcet's disease (BD) is a chronic multi-systemic inflammatory disorder characterised by oro-genital ulcers, cutaneous manifestations, ocular, vascular, neurologic and gastrointestinal involvement. Complex interactions operating on the genetic background e.g.(HLA51), of infectious and other environmental agents, together with immune dysregulation impacts on the pathogenesis of BD. This suggests that the environmental factors triggering immune responses may activate clinical manifestations in genetically susceptible individuals. Since oral health forms the basis of all general health both dental and systemic, it is an important component of both Dentistry and Medicine. Oral ulcers are the most common clinical manifestation of oral mucosal health. Changes in the oral environment consequently acts as an infective and immune trigger. In this review, complex interactions between the oral ulcers, the oral microbiome and immune responses together with the course of oral and systemic disease manifestations in BD are discussed in the context of the aetiologic role of oral health.
Keywords: oral health; aetiology; oral ulcer; immune response; Behcet's disease; PERIODONTAL FINDINGS; TURKISH PATIENTS; STREPTOCOCCUS-SANGUIS; INFECTIOUS ETIOLOGY; SALIVARY LEVELS; ULCER ACTIVITY; HNP 1-3; MICROBIOME; ASSOCIATION; PREVALENCE